Double photoexcitation of He atoms by attosecond xuv pulses in the presence of intense few-cycle infrared lasers - Tong, X. M.; Lin, C. D. (My University, 2005)
We studied the photoelectron spectra of He atoms resulting from double photoexcitation to autoionizing states by an attosecond xuv pulse in the presence of intense few-cycle Ti:sapphire lasers using the time-dependent hyperspherical close-coupling method. In its first application we show that the combination of a weak xuv pulse and an intense infrared laser offers an efficient means for probing states that cannot be reached by single photoabsorption experiments alone. The method provides an alternative approach of studying Stark induced states at field strength much higher than that available for a dc electric field. Using parameters from the presently available attosecond pulses and infrared lasers we showed that the four singlet 2ℓ2ℓ′ doubly excited states of He are prominently excited in such experiments. The dependence of the shape of the autoionizing states thus generated has been studied with respect to the intensity and the carrier-envelope phase of the few-cycle laser pulses.